Returns in the Labor Market: A Nuanced View of Penalties at the Intersection of Race and Gender in the US. - Paul, Mark; Zaw, Khaing; Darity, William (Feminist Economics, 2022)
There have been decades of research on wage gaps for groups based on their socially salient identities, such as race and gender, but little empirical investigation on the effects of holding multiple identities. Using the Current Population Survey, this study provides new evidence on intersectionality and the wage gap in the US. This article makes two important contributions. First, there is no single "gender" or "race" wage penalty. Second, the evidence suggests that holding multiple identities cannot readily be disaggregated in an additive fashion. Instead, in a comparison of Black and White workers across gender, this study documents that the penalties associated with the combination of two or more socially marginalized identities interact in multiplicative or quantitatively nuanced ways. Further, the findings demonstrate that the presence of an additional intersectional penalty for Black women persists across time. HIGHLIGHTS When it comes to earnings, Black women face distinctive penalties for holding their race and gender identities simultaneously. The intersectional wage gap persists across time and during both tight and slack labor markets. The unexplained portion of the wage gap has contracted from 1980–2017; however, it remains large and significant. Intersectional analysis provides a useful framework to disentangle nuances in the labor market.